Note of "Stocks" and "Flows" in Monetary Interest Theory - Fellner, William; Somers, Harold M. (The Review of Economics and Statistics, 1949)
We had divided the demand for money during a period of time according to the method used to satisfy that demand: sale of goods, sale of securities, and keeping money already held. Obviously the first two constituents involve flow-analysis in the usual sense money, goods, and securities must change hands during the period to satisfy the demand for money. Nor is it the intention of the demanders to